For Some, Luck Matters More: The Impact of the Great Recession on the Early Careers of Graduates from Different Socio-Economic Backgrounds - Emilia Del Bono; Greta Morando (Institute of Labor Economics (IZA), 2021)
This paper uses variation in unemployment caused by the 2008 recession to analyse socio- economic gaps in graduate outcomes. Our data comes from a survey which collects information on several cohorts of students from all English universities and reports their destinations at 6 months after graduation. The results show that when students from less advantaged family backgrounds graduate during a recession they are more likely to become unemployed, to work part-time, and to earn less than students from more advantaged families. There is evidence that professional networks established while at university are important in explaining some of these socio-economic gaps in outcomes.
Keywords: E32; I23; I24; I26; J62; 330; graduate employment; socio-economic gap; recession